Advance Import Processing: A bibliometric study of Scopus - Espinoza-Casco, Roque Juan (2023)
The aim of this study was to conduct a bibliometric analysis of the literature on advance customs clearance published in Scopus between 2006 and 2023. It was a bibliometric data study to measure scientific production through indicators. Keywords in English (advance, customs, clearance) were used to select 74 Scopus documents relevant to the study. According to the results, scientific production peaked in 2018, 2016 and 2012 (n=22; 29.7%). In addition, the United States accounted for 28.1% of all publications (n=32), 9 papers were published in Journal of International Economics and the most cited author was Manova, K. (481 citations; n=2 papers). The vast majority of these publications (92%) were research papers in the fields of economics, econometrics and finance (43%), social sciences (20%) and business, management and accounting (14%). It is concluded that the study conducted on advance customs clearance has a general upward trend, in terms of the breadth of topics covered, resources available and the number of authors who have made significant contributions to the area. This represents the basis for future research establishing a written argument and using the bibliometric study as a starting point.